2020
DOI: 10.3389/fonc.2020.01691
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-Particle Radiation on Intercellular Communication Networks of Tunneling Nanotubes in U87 Glioblastoma Cells

Abstract: Cellular communication plays a crucial role in the coordination and organization of cancer cells. Especially processes such as uncontrolled cell growth, invasion, and therapy resistance (development), which are features of very malignant tumors like glioblastomas, are supported by an efficient cell-to-cell communication in the tumor environment. One powerful way for cells to communicate are tunneling nanotubes (TNTs). These tiny membrane tunnels interconnect cells over long distances and serve as highways for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In 1992, Nagasawa and Little were the first to show the involvement of bystander effects in alpha particle irradiation in CHO cells irradiated with low fluences of alpha particles produced by 238 Pu (57). Their findings were confirmed and expanded by many other researchers (58)(59)(60)(61). They observed that sister chromatid exchanges were increased in 30% of cells, although only 1% of nuclei were traversed by particles.…”
Section: Revisiting the Target Cell Theory: Involvement Of Bystander Effectssupporting
confidence: 75%
“…In 1992, Nagasawa and Little were the first to show the involvement of bystander effects in alpha particle irradiation in CHO cells irradiated with low fluences of alpha particles produced by 238 Pu (57). Their findings were confirmed and expanded by many other researchers (58)(59)(60)(61). They observed that sister chromatid exchanges were increased in 30% of cells, although only 1% of nuclei were traversed by particles.…”
Section: Revisiting the Target Cell Theory: Involvement Of Bystander Effectssupporting
confidence: 75%
“…Interestingly, we recently showed that TNTs formed by healthy astrocytes or by GBM cells display structural differences in terms of length and thickness, which reflect different transport efficiencies [123]. A recent paper showed that irradiated U87 GBM cells quickly establish a network of cell-to-cell connections with high TNT content in comparison with non-irradiated cells, suggesting that the TNT formation may be also a consequence of treatment [124].…”
Section: Formation Of Tnts In Gbmmentioning
confidence: 99%
“…Tissue damage, localized at a drug injection site or to the larger area of tumor resection, was also identified as sufficient cellular stress to trigger TNT formation [ 31 , 47 ]. Moreover, cancer therapy itself can constitute a tissue insult sufficient to stimulate TNT formation, as shown following α-particle radiation of U87 glioblastoma cell line or doxorubicin, cytarabine and temozolomide chemotherapeutic treatments in human pancreatic cell lines, human AML blasts and human glioblastoma cell lines respectively [ 33 , 48 , 68 , 69 ].…”
Section: Molecular Determinants Of Tnt Formation and Cargo Intercellu...mentioning
confidence: 99%